A novel EWS‐CREB3L3 gene fusion in a mesenteric sclerosing epithelioid fibrosarcoma. Issue 9 (1st July 2017) - Dewaele, Barbara; Libbrecht, Louis; Levy, Gabriel; Brichard, Benedicte; Vanspauwen, Vanessa; Sciot, Raf; Debiec‐Rychter, Maria
Abstract: Sclerosing epithelioid fibrosarcoma (SEF) is a rare, malignant fibroblastic neoplasm, morphologically composed of cords, nests or sheets of monotonous epithelioid cells within a collagenous matrix. It has been recently characterized by recurrent pathogenic EWS ‐ CREB3L1/2 or FUS ‐ CREB3L2 fusions and common MUC4 protein expression by immunohistochemistry. Typically SEF occur in middle‐aged adults and rarely have been reported within the abdominal cavity. Here we report an 18‐year‐old man with intraabdominal tumor and multiple disseminated liver metastases, presenting pure SEF histologic and immunophenotypic features. Fluorescence in situ hybridization analysis showed unbalanced rearrangement of Ewing sarcoma breakpoint region 1 (EWSR1) gene. Genomic profiling by array CGH, followed by RT‐PCR and sequencing analysis, revealed a previously not reported EWSR1 translocation partner, cAMP‐responsive element‐binding protein 3‐like 3 ( CREB3L3 ). The novel EWSR1‐CREB3L3 fusion further extends the range of fusion types involving EWSR1 that are characteristic for SEF.